EVALUASI UJI KETURUNAN HALF-SIB Shorea leprosula MIQ. UMUR 6 TAHUN DI PT. SARMIENTO PARAKANTJA TIMBER KALIMANTAN TENGAH - , NANIK ZULAILA. S.HUT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The half-sib progeny test of Shorea leprosula Miq. in PT. Sarmiento Parakantja Timber (PT. Sarpatim) Central Kalimantan, was established to convert into an half-sib seedling seed orchard by reason of quality seed availability was lacking. The aims of this research were to assess variation and estimate genetic parameters of growth, as well as to identify the rouging impact in genetic parameters of S. leprosula. Materials of S. leprosula were collected from 72 families (60 families from PT. Sarpatim, 4 families from PT. SJM, 7 families from PT. SBK, and 1 family from PT. Erna Djuliawati) with 4 treeplots each family. The trials were planted using a Randomized Complete Block Design (RCBD), with ten replications, and 6 m x 3 m in plants spacing. The result showed that the growth of S. leprosula progeny test was fast at 6 years old (a mean height 12,46 Â± 2,47 m and a mean diameter 14,34 Â± 3,131 cm). Statistically significant differences in height and diameter were not detected among families (Fheight=1 and Fdiameter=0,9